Root canal filling material premixed with nano niobium silicate and preparation method of root canal filling material

By premixing the root canal filling materials with components such as niobium silicate, the problems of long curing time, low early strength and insufficient biological activity of existing materials are solved, and the curing time is shortened, compressive strength and biological activity are improved. Effect, suitable for dental root canal filling.

CN119424218AActive Publication Date: 2025-02-14BEOGENE BIOTECH GUANGZHOU

Patent Information

Application Number
CN202411630740.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-14
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing root canal filling materials have shortcomings in terms of excessive curing time, low early strength, insufficient biological activity and poor clinical operation performance, which is difficult to meet the high standards of dental treatment.

Method used

Using premixed nanoniobium silicate root canal filling material, a high-efficiency root canal is formed by premixing nanoniobium silicate powder, calcium silicate powder, X-ray retardant filler and excipient in a specific proportion. Filling material.

Benefits of technology

It significantly shortens the curing time, improves the compressive strength after curing, enhances the fluidity and retardant effect of the material, improves the biological activity and clinical operation performance, and improves the repair and regeneration effect after the root apical alveolar bone defect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424218A_ABST
    Figure CN119424218A_ABST
Patent Text Reader

Abstract

The invention relates to a root canal filling material premixed with nano niobium silicate and a preparation method of the root canal filling material. The filling material is prepared from a) nano niobium silicate powder; b) calcium silicate compound powder; c) an X-ray radiation-resistant filler; the dosage of the component a) is 1-10% by mass, and the sum of the dosage of the component a), the dosage of the component b) and the dosage of the component c) is 40-90% by mass. According to the filling material disclosed by the invention, a proper amount of nano niobium silicate is introduced, so that the curing time can be remarkably shortened, the flowability is improved, the filling material can be bonded with tissues around a root canal, repair and regeneration of dentin are actively promoted in combination with the nano niobium silicate, and compared with an existing material, repair and regeneration after defect of an apical alveolar bone can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical materials, and in particular relates to a root canal filling material premixed with nano-niobium silicate and a preparation method thereof. Background Art

[0002] Root canal therapy is an effective method for treating pulp disease and periapical periodontitis, and root canal filling materials are the key to successful treatment. Ideal dental filling materials must have good biocompatibility, antibacterial and clinical operability. In addition, biological activity is also used as a basis for measuring the bonding performance between the material and the tooth body. However, the materials currently used in clinical practice have certain shortcomings. Calcium hydroxide-based materials are widely used in dental pulp as pulp capping agents, root canal disinfectants, and root canal filling materials, but they have strong cytotoxicity, weak solubility and diffusivity, do not have solidification and molding characteristics, are prone to particle release, lack of biological activity, and increase the risk of dentin fracture; the performance of new calcium silicate materials such as MTA has been improved to a certain extent, and they are now widely used in clinical practice as pulp capping agents and root canal sealers, but they solidify slowly and have low early strength.

[0003] Chinese patent (publication number CN101668550A) "Premixed biological hydraulic cement paste composition and its application" discloses a premixed cement paste that can be used for medical or dental purposes. The patent premixes tricalcium silicate, dicalcium silicate and an organic solvent, which is convenient for doctors to use, but the coagulation time is too long, and some require 72 hours to coagulate. The long coagulation time not only causes the patient to wait longer, but also makes the operation more complicated. Chinese patent (publication number CN102049062 A) "Injectable, efficient, suspended and stable calcium phosphate bone cement and its preparation method and application" discloses an injectable calcium phosphate bone cement material system. The patent improves the suspension stability of the calcium phosphate bone cement premix system by adding fumed silica and its modified products. The disadvantage is that the calcium phosphate bone cement is not strong enough and is easy to break.

[0004] Based on this, it is necessary to further develop a premixed root filling material with short setting time, high strength, higher biological activity and better clinical operation performance.

[0005] Nano-niobium silicate is an emerging material with excellent osteogenic effect and good biocompatibility. Studies have found that nano-niobium silicate can significantly enhance the early osteogenic differentiation and later mature mineralization in the bone repair process. At the same time, niobium silicate has excellent chemical stability and high mechanical strength, and is expected to be used in bone repair materials. Summary of the invention

[0006] In view of the above-mentioned current technical deficiencies, the present invention provides a root canal filling material of premixed nano-niobium silicate and a preparation method thereof.

[0007] The technical solution of the present invention is as follows:

[0008] In a first aspect, the present invention provides a root canal filling material of premixed nano-niobium silicate, which is composed of a) nano-niobium silicate powder; b) calcium silicate compound powder; c) X-ray blocking filler; and d) excipient. In terms of mass percentage, the amount of component a) is 1-10%, and the sum of the three components a), b) and c) is 40-90%.

[0009] Preferably, the sum of the three components a), b) and c) is 60-80%. In a preferred embodiment, the sum of the three components a), b) and c) is 70%.

[0010] More preferably, the content of component a) is 2.5-7%.

[0011] Further preferably, the root canal filling material of the present invention consists of 2.5-7% a), 40%-50% b), 10-20% c) and the balance d).

[0012] Preferably, the calcium silicate compound is at least one of tricalcium silicate, dicalcium silicate and calcium silicate.

[0013] Preferably, the X-ray blocking filler is at least one of zirconium oxide, barium sulfate, tantalum oxide and bismuth oxide.

[0014] Preferably, the excipient is at least one of ethylene glycol, polyethylene glycol, propylene glycol, glycerol, ethanol, vegetable oil, animal oil, silicone oil, and hydroxypropyl methylcellulose. In some preferred embodiments, the excipient consists of hydroxypropyl methylcellulose and polyethylene glycol.

[0015] The second aspect of the present invention further provides a method for preparing the root canal filling material, comprising the following steps:

[0016] Step 1: Mix and disperse component d) to obtain phase A;

[0017] Step 2: Add component c) into phase A and disperse evenly to obtain a suspension;

[0018] Step 3: Add components a) and b) to the above suspension and disperse evenly to form a paste.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1) Greatly shortened curing time: Traditional root canal filling materials take too long to cure, and some take 72 hours to solidify. At the same time, the compressive strength of the materials is poor in the initial curing stage. However, the calcium silicate-based root canal filling material premixed with nano-niobium silicate provided by the present invention has a curing time of only 2.5-6 hours, and the compressive strength is significantly enhanced after curing.

[0021] 2) Enhanced fluidity: After premixing with nano-niobium silicate, the fluidity of the material is enhanced, making it easier to enter the lateral root canal and the root apex, thereby improving the marginal sealing of the root canal.

[0022] 3) Enhanced radiation blocking effect: After pre-mixing with nano-niobium silicate, the radiation blocking effect of the original material is significantly enhanced.

[0023] In summary, the filling material of the present invention improves fluidity and shortens curing time by optimizing the formula. The filling material can form a tight bond with the tissue surrounding the root canal during filling. Since nano-niobium silicate actively promotes the repair and regeneration of dentin, it can significantly improve the repair and regeneration of apical alveolar bone defects compared to existing materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a photograph of the sample obtained from Example 2;

[0025] Figure 2 SEM image of the sample obtained in Example 2 after curing;

[0026] Figure 3 Schematic diagram of X-ray blocking effect. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0028] Example 1

[0029] A root canal filling material of premixed nano-niobium silicate is composed of the following components in percentage by mass: 7% nano-niobium silicate, 45% calcium silicate, 18% zirconium oxide, 22% polyethylene glycol and 8% hydroxypropyl methylcellulose.

[0030] The preparation method thereof comprises the following steps:

[0031] Step 1: Add hydroxypropyl methylcellulose to polyethylene glycol, stir and dissolve to obtain phase A;

[0032] Step 2: Add zirconium oxide to phase A and stir until evenly dispersed to obtain a suspension;

[0033] Step 3: Add nano-niobium silicate and calcium silicate to the above suspension, and stir evenly until a paste is formed, thereby obtaining a calcium silicate root canal filling material premixed with nano-niobium silicate.

[0034] Example 2

[0035] A root canal filling material of premixed nano-niobium silicate is composed of the following components in percentage by mass: 2.5% nano-niobium silicate, 49.5% calcium silicate, 18% zirconium oxide, 25% polyethylene glycol and 5% hydroxypropyl methylcellulose.

[0036] The preparation method thereof comprises the following steps:

[0037] Step 1: Add hydroxypropyl methylcellulose to polyethylene glycol, stir and dissolve to obtain phase A;

[0038] Step 2: Add zirconium oxide to phase A and stir until evenly dispersed to obtain a suspension;

[0039] Step 3: Add nano-niobium silicate and calcium silicate to the above suspension, and stir evenly until a paste is formed, thereby obtaining a calcium silicate root canal filling material premixed with nano-niobium silicate.

[0040] Example 3

[0041] A root canal filling material of premixed nano-niobium silicate is composed of the following components in percentage by mass: 5% nano-niobium silicate, 50% calcium silicate, 15% zirconium oxide, 25% polyethylene glycol and 5% hydroxypropyl methylcellulose.

[0042] The preparation method thereof comprises the following steps:

[0043] Step 1: Add hydroxypropyl methylcellulose to polyethylene glycol, stir and dissolve to obtain phase A;

[0044] Step 2: Add zirconium oxide to phase A and stir until evenly dispersed to obtain a suspension;

[0045] Step 3: Add nano-niobium silicate and calcium silicate to the above suspension, and stir evenly until a paste is formed, thereby obtaining a calcium silicate root canal filling material premixed with nano-niobium silicate.

[0046] Comparative Example 1

[0047] A dental root canal filling material consists of the following components in percentage by mass: 50% calcium silicate, 18% zirconium oxide, 27% polyethylene glycol and 5% hydroxypropyl methylcellulose.

[0048] The preparation method thereof comprises the following steps:

[0049] Step 1: Add hydroxypropyl methylcellulose to polyethylene glycol, stir and dissolve to obtain phase A;

[0050] Step 2: Add zirconium oxide to phase A and stir until evenly dispersed to obtain a suspension;

[0051] Step 3: Add calcium silicate to the above suspension and stir evenly until a paste is formed to obtain a premixed calcium silicate root canal filling material.

[0052] Comparative Example 2

[0053] A root canal filling material of premixed nano-niobium silicate is composed of the following components in percentage by mass: 15% nano-niobium silicate, 37% calcium silicate, 18% zirconium oxide, 25% polyethylene glycol and 5% hydroxypropyl methylcellulose.

[0054] The preparation method thereof comprises the following steps:

[0055] Step 1: Add hydroxypropyl methylcellulose to polyethylene glycol, stir and dissolve to obtain phase A;

[0056] Step 2: Add zirconium oxide to phase A and stir until evenly dispersed to obtain a suspension;

[0057] Step 3: Add nano-niobium silicate and calcium silicate to the above suspension, and stir evenly until a paste is formed, thereby obtaining a calcium silicate root canal filling material premixed with nano-niobium silicate.

[0058] Table 1: Examples and Comparative Examples

[0059] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Nano Niobium Silicate 7 2.5 5 0 15 Calcium silicate 45 49.5 50 50 37 Zirconia 18 18 15 18 18 Polyethylene glycol 22 25 25 27 25 Hydroxypropyl methylcellulose 8 5 5 5 5

[0060] Performance Testing

[0061] 1. Curing time

[0062] Prepare the apparatus according to the requirements of 7.5.1 of YY0717-2023 standard. Place the mold in an environment of 37°C and 95% relative humidity for 24 hours, then fill the pre-treated mold cavity with the materials of Examples 1-3 and Comparative Examples 1-2, respectively, take 3 products for parallel testing, and test according to 7.5.3 of YY0717-2023 to obtain the curing time.

[0063] The results are shown in Table 2. As can be seen from Table 2, the curing time of the filling paste premixed with a certain amount of nano-niobium silicate is significantly shorter than that of the product of Comparative Example 1 that is not mixed with nano-niobium silicate. However, when the content of niobium silicate is too high, the curing time is not significantly shortened. It can be seen that the filling paste premixed with nano-niobium silicate provided by the present invention significantly shortens the curing time, which is conducive to achieving high-quality clinical filling effects. Among them, the sample in Example 2 has the shortest curing time, Figure 1 The filling material sample picture obtained for Example 2, Figure 2This is a SEM picture of the filling material of Example 2 after curing. It can be seen that after hydraulic curing, the structure is dense and can form a tight bond with the tissue around the root canal.

[0064] 2. Liquidity test

[0065] The filling pastes prepared in Examples 1-3 and Comparative Examples 1-2 were respectively subjected to flowability tests according to the standard requirements of YY / T0717-2009 “Dental Root Canal Sealing Materials”.

[0066] The results are shown in Table 2. Compared with Comparative Example 1, Examples 1-3 significantly improve the fluidity of the filling material, making it easier for the product to enter the lateral root canal and the root apex. However, the fluidity of Comparative Example 2 is too high, and there is a risk of overfilling in clinical practice.

[0067] Table 2 Curing time and fluidity of different embodiments and comparative examples

[0068] serial number Sample name Curing time (h) Flowability(mm) 1 Example 1 5h 24.42 2 Example 2 3h 22.61 3 Example 3 3.5h 25.28 4 Comparative Example 1 18h 17.25 5 Comparative Example 2 12h 28.89

[0069] 3. Radiation resistance test

[0070] Take 0.05 mL of the samples of Example 2, Comparative Example 1, and Comparative Example 2 respectively, make discs with a diameter of about 10 mm, put them into the center of the X-ray film after curing, and perform X-ray photography with reference to YY0717-2023 to obtain an X-ray grayscale comparison diagram.

[0071] The results are as follows Figure 3 As shown. Figure 3 The results show that the filling paste premixed with a certain amount of nano-niobium silicate in Example 2 improves the X-ray blocking effect compared with Comparative Example 1. Comparative Example 2 has better X-ray blocking performance and improves hardness at the same time, but causes cracking of the product after curing.

[0072] From the above, it can be seen that the calcium silicate root canal filling material premixed with nano-niobium silicate of the present invention significantly reduces the curing time by introducing nano-niobium silicate and coordinating with other components, and the compressive strength is significantly enhanced after curing. In addition, the material fluidity is increased, making it easier to enter the lateral root canal and the root apex, forming a better filling effect. At the same time, nano-niobium silicate also enhances the radiation blocking effect of the original material.

[0073] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0074] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A root canal filling material premixed with nano-niobium silicate, characterized in that: It consists of a) nano-niobium silicate powder; b) calcium silicate compound powder; c) X-ray blocking filler; d) Excipient composition: in terms of mass percentage, the content of component a) is 1-10%, and the sum of components a), b) and c) is 40-90%.

2. The root canal filling material according to claim 1, characterized in that: The sum of the three components a), b) and c) is 60-80%.

3. The root canal filling material according to claim 2, characterized in that: The content of component a) is 2.5-7%.

4. The root canal filling material according to claim 3, characterized in that: It consists of 2.5-7% a), 40%-50% b), 10-20% c) and the balance d).

5. The root canal filling material according to claim 1, characterized in that: The calcium silicate compound is at least one of tricalcium silicate, dicalcium silicate and calcium silicate.

6. The root canal filling material according to claim 1, characterized in that: The X-ray blocking filler is at least one of zirconium oxide, barium sulfate, tantalum oxide and bismuth oxide.

7. The root canal filling material according to claim 1, characterized in that: The excipient is at least one of ethylene glycol, polyethylene glycol, propylene glycol, glycerol, ethanol, vegetable oil, animal oil, silicone oil, and hydroxypropyl methylcellulose.

8. The root canal filling material according to claim 1, characterized in that: The excipients are hydroxypropyl methylcellulose and polyethylene glycol.

9. The method for preparing a root canal filling material according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: Mix and disperse component d) to obtain phase A; Step 2: Add component c) into phase A and disperse evenly to obtain a suspension; Step 3: Add components a) and b) to the above suspension and disperse evenly to form a paste.

Citation Information

Patent Citations

  • Premixed biological hydraulic cement paste composition and using the same

    CN101668550A

  • Injectable efficient suspended stable calcium phosphate cement and preparation method and application thereof

    CN102049062A

  • Premixed calcium silicate based root canal filling material with suspension stability as well as preparation method and application thereof

    CN107080697A

  • Pre-mixed calcium silicate / magnesium phosphate double-phase composite self-solidification root canal filling material and preparation method and application thereof

    CN107411976A

  • Biomimetic mineral based endodontic cement composition and uses thereof

    US20170340523A1

Cited By

  • Composite root canal filling agent of premixed calcium silicate-niobium compound as well as preparation method and application of composite root canal filling agent

    CN121015458A